Effects of Dried on Some Properties of Strawberry Tree Fruits - DEMIRSOY, HUSNU; DEMIRSOY, LEYLA; CELIKEL, GULAY; KOYUNCU, TURHAN (Asian Journal of Chemistry, 2010)
In the fruits of two different genotypes (57A1 and 57A22) of Turkish strawberry trees (Arbutus unedo L.) dried at 70 and 80 °C in a computer connected parallel air flow type drier, fruit weight, fruit color and vitamin C were determined. In this study, it was determined that drying increased losses of fruit weight and Vitamin C, and soluble solid content and also colour variations in dried fruits occurred. In both genotypes, the drying at 70°C temperature was better than 80°C in terms of fruit weight, vitamin C, soluble solids and colour.